Caries Increment and Oral Hygiene Changes in 6- and 12-Year-Old Children in Riga, Latvia: A 3–Year Follow–Up Report Using ICDAS II and RADKE Criteria - Gudkina, Jekaterina; Amaechi, Bennett T.; Abrams, Stephen. H.; Brinkmane, Anda; Jelisejeva, Ieva (European Journal of Dentistry, 2019)
Objectives The purpose of this study was to investigate the caries increment and oral hygiene changes over a 3-year period and also compare the sensitivity and specificity of Radke’s caries assessment method to ICDAS II among 6- and 12-year-old children in Riga, Latvia.Materials and Methods Thirty-eight 6 and thirty-nine 12-year-old children were examined visually and with bitewing (BW) radiographs for dental caries at baseline and after a 3-year period. Decayed, missing, and filled surfaces (dmfs/DMFS) in all teeth were scored by one calibrated examiner using the Radke’s caries scoring criteria. Oral hygiene level was determined using Green-Vermillion index (G-V ind.) at baseline and after 3 years. ICDAS II was used to assess all children only at the 3rd-year time point. The parents of the 6- and 12-year-old children responded to a questionnaire on oral hygiene at baseline and at the 3-year mark.Statistical Analysis The data were analyzed using t-test, Chi-square test, Wilcoxon test (α= 0.05), and sensitivity and specificity tests.Results The mean (SD) values of G–V ind. and caries experience at baseline/3-year period in 6- versus 12-year-old children were as follows. G-V ind.: 1.14(0.80) /1.48(0.89) [p = 0.4768] versus 0.99(0.45)/1.45(1.22) [p = 0.0337]. DMFS: 0.72(1.02)/ 3.13(3.13) [p = 0.0000] versus 6.79(5.14)/14.79(9.86)[p = 0.0000]; dmfs: 11.26(8.71)/7.74 (4.86) [p = 0.0780] versus 3.57 (2.03)/1.5(0.71)[p = 0.3173].The sensitivity and specificity of Radke to ICDAS II of caries-affected surfaces was: in proximal surfaces–0.57 and 0.98, on occlusal surfaces–0.83 and 0.98, on buccal/lingual surfaces–0.43 and 0.99.Conclusions The result of the present study suggests that the increased caries experience over a 3-year period among the 6- and 12-year-old children in Riga may be due to the concurrent decreased level of oral hygiene, suggesting that ICDAS II instead of Radke’s criteria should be used to detect and monitor dental caries.
Keywords: caries experience; oral hygiene; sensitivity; specificity; caries prevalence